Instructions for Building a Bubble: Managing the return to in-person learning and teaching work in secondary schools in the AMBA region (Praxis Educativa, 2026)
This article analyzes the return to in-person classes in the Buenos Aires Metropolitan Area after the COVID-19 lockdown, focusing on the impact of the bubble model on school organization and teachers’ work. Based on a sociological approach and fieldwork in six secondary schools, the study reveals how the simultaneity of in-person and virtual classes blurred the boundaries of work time and space, leading to an unsustainable workload. From a socio-anthropological perspective, it also explores the role of emotions, especially fear, in the reconfiguration of school spaces. The study highlights the tensions faced by teachers and school leaders and evidences teachers' skepticism about the effectiveness of educational policies, often perceived as a "simulation" in response to urgent demands. The findings underscore the importance of educational policies having clear objectives and shared meanings to achieve sustainable transformations in the education system.
Keywords: secondary school; high school; health bubble; teaching work; management team; emotions